Livestock without frontiers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
study visit on livestock and the meat trade in West and Central Africa, organised by CTA in Burkina Faso and Côte d Ivoire at the end of March 2000